An introduction to particle dark matter - Profumo, Stefano 1978- (Hackensack, NJ World Scientific, 2017)
"What is the dark matter that fills the Universe and binds together galaxies? How was it produced? What are its interactions and particle properties? The paradigm of dark matter is one of the key developments at the interface of cosmology and elementary particle physics. It is also one of the foundations of the standard cosmological model. This book presents the state of the art in building and testing particle models for dark matter. Each chapter gives an analysis of questions, research directions, and methods within the field. More than 200 problems are included to challenge and stimulate the reader's knowledge and provide guidance in the practical implementation of the numerous "tools of the trade" presented. Appendices summarize the basics of cosmology and particle physics needed for any quantitative understanding of particle models for dark matter. This interdisciplinary textbook is essential reading for anyone interested in the microscopic nature of dark matter as it manifests itself in particle physics experiments, cosmological observations, and high-energy astrophysical phenomena: from graduate students and advanced undergraduates to cosmologists and astrophysicists interested in particle models for dark matter and particle physicists interested in early-universe cosmology and high-energy astrophysics"--
Particle dark matter: the name of the game -- The thermal relic paradigm: zeroth-order lessons from cosmology -- The thermal relic paradigm: a closer look -- The art of WIMP direct detection -- Indirect dark matter searches -- Searching for dark matter with particle colliders -- Axions and axion-like particles as dark matter -- Sterile neutrinos as dark matter particles -- Bestiarium: a short, biased compendium of notable dark matter particle candidates and models
Includes bibliographical references (pages 251-265) and index
13
Keywords: Dark matter (Astronomy); Particles (Nuclear physics)